Sintering kinetics of ZrO2 nanopowders modified by group IV elements. Issue 4 (12th March 2019) - Lakusta, Marharyta; Danilenko, Igor; Volkova, Galina; Loladze, Larisa; Burkhovetskiy, Valeriy; Doroshkevich, Oleksandr; Brykhanova, Irina; Popova, Inna; Konstantinova, Tetyana
Abstract: The sintering behavior of tetragonal zirconia nanopowders modified by the group IV elements at the initial sintering stage was investigated. It was found that different additives SiO2, SnO2, and GeO2 have a significant influence on the densification kinetics of 3Y‐TZP nanopowders obtained by coprecipitation during sintering as it depends on the amount of additives (0‐5 wt%). The shrinkage of zirconia‐based specimens during the nonisothermal sintering was analyzed using the dilatometric data. The constant rate of heating technique was applied in order to determine the dominant mass transfer mechanism at the initial stage of sintering in modified zirconia nanopowders. It was found that there was a change in the mass transfer mechanism and diffusion activation energy in 3Y‐TZP as a result of the additives. The dominant sintering mechanism in 3Y‐TZP changed from the volume diffusion to the grain boundary diffusion due to the addition of SiO2 and SnO2 and the sintering activation energy increased in these cases. However, GeO2 additive activated the viscous flow mechanism in sintering process of 3Y‐TZP nanopowders which led to acceleration of the densification due to the decrease in the diffusion activation energy.